The polymict carbonaceous breccia Aguas Zarcas: A potential analog to samples being returned by the OSIRIS‐REx and Hayabusa2 missions. (2nd February 2021) - Kerraouch, Imene; Bischoff, Addi; Zolensky, Michael E.; Pack, Andreas; Patzek, Markus; Hanna, Romy D.; Fries, Marc D.; Harries, Dennis; Kebukawa, Yoko; Le, Loan; Ito, Motoo; Rahman, Zia
Abstract: On April 23, 2019, a meteorite fall occurred in Aguas Zarcas, Costa Rica. According to the Meteoritical Bulletin, Aguas Zarcas is a brecciated CM2 chondrite dominated by two lithologies. Our X‐ray computed tomography (XCT) results show many different lithologies. In this paper, we describe the petrographic and mineralogical investigation of five different lithologies of the Aguas Zarcas meteorite. The bulk oxygen isotope compositions of some lithologies were also measured. The Aguas Zarcas meteorite is a breccia at all scales. From two small fragments, we have noted five main lithologies, including (1) Met‐1: a metal‐rich lithology; (2) Met‐2: a second metal‐rich lithology which is distinct from Met‐1; (3) a brecciated CM lithology with clasts of different petrologic subtypes; (4) a C1/2 lithology; and (5) a C1 lithology. The Met‐1 lithology is a new and unique carbonaceous chondrite which bears similarities to CR and CM chondrite groups, but is distinct from both based on oxygen isotope data. Met‐2 also represents a new type of carbonaceous chondrite, but it is more similar to the CM chondrite group, albeit with a very high abundance of metal. We have noted some similarities between the Met‐1 and Met‐2 lithologies and will explore possible genetic relationships. We have also identified a brecciated CM lithology with two primary components: a chondrule‐poor lithology and a chondrule‐rich lithology showing different petrologic subtypes. The other two lithologies, C1 and C1/2, are very altered and possibly related to the CM chondrite group. In this article, we describe all the lithologies in detail and attempt a classification of each in order to understand the origin and the history of formation of the Aguas Zarcas parent body.